UNVEILING ANTIFUNGAL PROTEINS FROM TRAMETES VERSICOLOR AS BIO-PESTICIDE TO INHIBIT ALTERNARIA SOLANI - ASHRAF, I; ALI, M; ASIF, M; ANWAR, W; AKHTAR, A; ALI, HA; BUKHARI, NT; ALI, Q; SHAFIQ, M (Biological and Clinical Sciences Research Journal, 2023)
Alternaria solani was isolated from infected tomato leaves, and Trametes versicolor from northern areas of Pakistan established mycelial culture on PDA. Crude Protein extract was prepared in 50mM Sodium phosphate buffer by macerating C. versicolor (T/C) mycelium. Extracted protein solution (Crude extract) was filtered and tested for antifungal activity by using different concentrations (0.5mg/ml, 1mg/ml, 1.5mg/ml, and 2mg/ml) against A. solani. A protein with antifungal potential was purified using the DEAE- Cellulose column followed by the gel filtration column of Superdex75. MIC was also observed for purified antifungal protein by using micro spectrophotometry. Results showed that T. versicolor has the potential to inhibit the fungal growth of A. solani. Crude extract with a concentration of 2mg/mL inhibited 83% of the growth of A. solani. However, only 47% of inhibition was observed in the case of 0.5mg/ml of protein extract. The protein having antifungal potential purified by anion exchange chromatography has an approximate size of 15 kDa. MIC for the purified protein is 200µg, which inhibited the 100% growth of A. solani.